Experimental Demonstration of High-Sensitivity Underwater Optical Wireless Communication Based on Photocounting Receiver - Chao Li (MDPI AG, 2021)
In this paper, we propose a high-sensitivity long-reach underwater optical wireless communication (UOWC) system with an Mbps-scale data rate. Using a commercial blue light-emitting diode (LED) source, a photon counting receiver, and return-to-zero on–off keying modulation, a receiver sensitivity of −70 dBm at 7% FEC limit is successfully achieved for a 5 Mbps intensity modulation direct detection UOWC system over 10 m underwater channel. For 1 Mbps and 2 Mbps data rates, the receiver sensitivity is enhanced to −76 dBm and −74 dBm, respectively. We further investigate the system performance under different water conditions: first type of seawater (c = 0.056 m−1), second type (c = 0.151 m−1), and third type (c = 0.398 m−1). The maximum distance of the 2 Mbps signal can be extended up to 100 m in the first type of seawater.